Motherhood, pregnancy or marriage effects? - Edo, María (2021)
The existence of large child penalties has been documented for multiple countries and time periods. In this paper, we assess to what extent marriage decisions and pregnancies (rather than live births), which tend to occur around the birth of the first child, explain part of the so-called motherhood effect in labor market outcomes. Using data for 29 countries drawn from SHARE, we show that although marriage has a negative effect on women’s employment (3.3%), its magnitude is much smaller compared with the negative effect of a first child (23%). Moreover, we find that pregnancies that end in non-live births have non-statistically significant effects in employment in the following years, supporting the exogeneity assumption underlying identification in child penalty studies. These new results lend support to the hypothesis that childcare, rather than marriage or pregnancy, is responsible for women exiting the labor force upon motherhood.